RETRACTED: The Novel Tumor Suppressor Gene ZNF24 Induces THCA Cells Senescence by Regulating Wnt Signaling Pathway, Resulting in Inhibition of THCA Tumorigenesis and Invasion - Xiong, Juan; Jiang, Panpan; Zhong, Li; Wang, Youling (Frontiers in Oncology, 2021)
Object Clinically, the effective treatment options available to thyroid cancer (THCA) patients are very limited. Elucidating the features of tumor suppressor genes (TSGs) and the corresponding signal transduction cascade may provide clues for the development of new strategies for targeted therapy of THCA. Therefore, this paper aims to explore the mechanism of ZNF24 underlying promoting THCA cell senescence at molecular level. Methods We performed RT-PCR and Western Blotting for evaluating associated RNA and protein expression. CCK8, colony forming, wound healing and Transwell chamber assays were conducted to examine THCA cell proliferation, invasion and migration. β-galactosidase staining assay was performed to detect THCA cells senescence. The size and volume of xenotransplanted tumors in nude mice are calculated to asses ZNF24 effect in vivo. Results Ectopic expression of ZNF24 significantly inhibited the cell viability, colony forming, migration and invasion abilities of THCA cell lines (K1/GLAG-66i and BCPAPi) (P < 0.05). ZNF24 induced BCPAPi cells senescence through regulating Wnt signaling pathway. ZNF24 inhibited Wnt signaling pathway activition by competitively binding β-catenin from LEF1/TCF1-β-catenin complex. In nude mice, both Ectopic expression of ZNF24 and 2,4-Da (the strong β-catenin/Tcf-4 inhibitor) treatment significantly decreased both the size and weight of xenotransplanted tumors when compared with control mice (P < 0.05). Conclusion Results obtained in vivo and in vitro reveal the role of ZNF24 in significantly suppressing THCA tumorigenesis and invasion by regulating Wnt signaling pathway.